Ten years of the Citizen's Electronic Health Record e-SUS Primary Healthcare: in search of an electronic Unified Health System - Ianka Cristina Celuppi; Eduarda Talita Bramorski Mohr; Mariano Felisberto; Thiago Serafim Rodrigues; Jades Fernando Hammes; Célio Luiz Cunha; Raul Sidnei Wazlawick; Eduardo Monguilhott Dalmarco (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE: Contextualize the adherence to the Prontuário Eletrônico do Cidadão (PEC - Citizen's Electronic Health Record) by Brazilian municipalities and the evolution of the electronic strategy of the Unified Health System (e-SUS) for Primary Healthcare (PHC) during its 10 years. METHODS: This descriptive study added information on adherence to the use of medical records extracted from the database of the Secretaria de Atenção Primária à Saúde (SAPS- Primary Healthcare Secretary) of the Federal Government between 2017 and 2022. We analized the number of computerized basic healthcare units that used some electronic medical records, the number of those that used simplified data collection (SDC), and those that implemented the citizen's electronic health record (PEC) in the same period. A descriptive synthesis of the functionalities and modules implemented in the system during its 10 years of development was also carried out. RESULTS: The adherence of Brazilian municipalities to the PEC has grown exponentially in the last five years, going from 8,930 healthcare units in 2017 to 26,091 in 2022. As expected, while the main functionalities and improvements developed in this decade sought to implement new flows and modules of administrative, clinical care, and care management processes and health service administration, improving aspects of usability and technological infrastructure of the application architecture was also crucial for the success of the system. CONCLUSIONS: In 2023, the milestone of a decade will be celebrated since the beginning of health records implementation by Brazilian municipalities, marked by technological and infrastructure challenges and improvements and new functionalities that highlight the technological evolution of the e-SUS PHC system and strategy. Despite many other tools, the PEC is arguably Brazil's leading electronic medical record today, as it has always invested in evolution, updating itself in technological and usability opportunities.